THE EFFECTS of The ALIENATION CULTURAL And the WAYS to CONFRONT It - Mahdi , Huthaifa (Islamic Sciences Journal, 2023)
When the researchers And Muslim thinkers talks about alienation, They refer to the daily reality of living scenes in the material, social psychological, cultural and civilization life , A reality created by difficult historical circumstances, And the combination of weaving yarns many factors, and given the depth of the phenomenon of Alienation in our contemporary cultural life, It is certain that the term " Alienation ", in its contemporary, well-known meaning, is the product of Western thought It is linked to the European imperialist movement that began in the 19th century. Therefore, the wave of Westernization aims to strike at the constants of the Islamic nation, and undermine the foundations of the Islamic community In order to be able to carry out its sabotage schemes, and pass their projects strictly controlled, And managed to create confusion and confusion in the Muslim family as the backbone of the Islamic community, The trend has managed to achieve a variety of goals and results; and found him supporters of the sons of Muslims promote his ideas and ideas in order to obtain wealth and reputation, And generated a range of expatriates who dazzled Western civilization with its glamor and deception..